2014
DOI: 10.1161/hypertensionaha.113.02204
|View full text |Cite
|
Sign up to set email alerts
|

The Value of N-Terminal Pro–B-Type Natriuretic Peptide in Determining Antihypertensive Benefit

Abstract: Abstract-We investigated 3 hypotheses: (1) N-terminal pro-B-type natriuretic peptide (NT-proBNP) predicts cardiovascular disease events in patients with hypertension, (2) NT-proBNP is associated with blood pressure variability, and (3) NT-proBNP predicts benefit from antihypertensive regimens. The Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT) randomized a subset of 6549 patients at risk with no history of coronary heart disease to either atenolol-based or amlodipine-based blood pressure-lowering treatment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
18
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 32 publications
4
18
0
Order By: Relevance
“…A recent study found that NT-proBNP was positively associated with visit-to-visit variability in BP determined as the SD of repeated office BP values [22]. That study may support our findings, although it was conducted in treated hypertensive patients with at least three other risk factors for cardiovascular disease [22].…”
Section: Discussionsupporting
confidence: 86%
“…A recent study found that NT-proBNP was positively associated with visit-to-visit variability in BP determined as the SD of repeated office BP values [22]. That study may support our findings, although it was conducted in treated hypertensive patients with at least three other risk factors for cardiovascular disease [22].…”
Section: Discussionsupporting
confidence: 86%
“…The risk of death with the highest NTproBNP tertile (≥133 pg/mL) was 3.3 times higher than the lowest tertile (<50.8 pg/mL) (HR, 3.30; 95% CI, 10.90-12.29). Similar findings have been reported by Welsh and colleagues 14 in hypertensive patients free of CHD at baseline from the Anglo-Scandinavian Cardiac Outcomes Trial (ASCOT). This study showed that NTproBNP predicted CVD risk independently of BP variation (odds ratio [OR], 1.24; 95% CI, 1.06-1.45).…”
Section: Studies Demonstrating the Value Of Bnps For The Detection Ofsupporting
confidence: 88%
“…The findings of the PONTIAC study are at variance with the findings of the much larger ASCOT study, in which the b-blockerbased regimen (atenolol) resulted in a significant increase (69.6%) in NT-proBNP levels compared with a significant decrease (36.5%) with the calcium channel blocker-based (amlodipine) regimen. 14 The increased NT-proBNP levels with b-blockers has been attributed to the increased diastolic filling time and to left ventricular stretch. In addition, the selection of the bblocker used in the PONTIAC study is questionable because of its adverse effects in glucose regulation.…”
Section: Treatment Of Residual Cardiovascular Riskmentioning
confidence: 99%
“…Although the baseline NT-proBNP levels in the present study were low and within normal limits, the extent of reduction in NT-proBNP levels was numerically greater with sacubitril/valsartan than with amlodipine or atenolol, despite a greater BP reduction, in the ASCOT study (Anglo-Scandinavian Cardiac Outcomes Trial). 41 The decrease in plasma aldosterone concentrations after treatment with both sacubitril/valsartan and valsartan is considered to be related to AT 1 receptor blockade and indicates that both treatments are conferring cardiovascular benefits owing to RAAS inhibition.…”
Section: Discussionmentioning
confidence: 99%